Relation between premenstrual symptoms and levels of depression measured by the Edinburgh Postnatal Depression Scale in women within their first year postpartum year. - Jaramillo-de-la-Riva-Agüero, Mariana (2022)
Objective: To evaluate the relationship between each symptom of premenstrual dysphoric disorder (PMDD) and the levels of postpartum depression (PPD). Methods: A secondary analysis of a database of 321 women evaluated cross- sectionally in the first postpartum year was conducted, determining the presence of PMDD symptoms according to the DSM-IV criteria, and the levels of PPD, using the Edinburgh Postnatal Depression Scale (EPDS). A bivariate analysis determined the variables significantly related to the EPDS scores, while a multivariate analysis helped to configure the best predictive model. Results: According to the bivariate analysis, headache (coefficient=3,26; p=0,002) and feeling overwhelmed (coefficient=4,95; p=0,003) are associated with higher scores in the EPDS, even more so than PMDD (coefficient=2,52; p<0,001) as a single variable. Other associated variables were history ofdepression (coefficient=2,42; p<0,001), having a partner (coefficient=1,54; p=0,041) and abortion (coefficient=1,44; p=0,034). The multivariate model that best predicts EPDS scores includes feeling overwhelmed, headache, history of major depression, having a partner, history of abortion and age. Conclusions: The above findings are significantly related to EPDS scores, which could be used to design screening scales for pregnant women, also taking into account other risk factors, such as age and past history of depression and abortion.